Effects of stage of maturity at harvest and kernel processing on the nutrient digestibility of corn silage - Wistuba, T.J.; Whitlock, L.A.; Siefers, M.K.; Bolsen, K.K.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve ruminally cannulated crossbred steers were used to evaluate the effects of stage of maturity and kernel processing (rolling) of whole-plant corn silage on nutrient digestibilities. The six silage rations were: 50% milkline, 80% milkline, and 7 days after-black layer (7BL) each ensiled processed (rolled) or unprocessed. Steers consuming the 80% milkline and 7BL processed rations had numerically higher DM and OM digestibilities, and all processed rations had numerically higher starch digestibilities. However, the three processed rations had numerically lower fiber digestibilities (NDF and/or ADF). Steers consuming the 80% milkline rations had numerically higher nutrient digestibilities than those fed the less or more mature silages. Yield data taken at each of the three harvests showed that whole-plant DM and grain yields increased with advancing maturity. The data indicate that harvesting at the 80% milkline stage of maturity and processing the whole-plant maximized DM yield and nutrient utilization.
Keywords: Beef; Mechanically processed; Corn silage; Stage of maturity; Growing cattle